2020
DOI: 10.1039/d0nj02994g
|View full text |Cite
|
Sign up to set email alerts
|

Novel formation of Au/Ag bimetallic nanoparticles from a mixture of monometallic nanoparticles and their application for the rapid detection of lead in onion samples

Abstract: The exposure, accumulation and contamination of heavy metals to humans and ecosystem through vegetables are serious health threats. One of the most important ingredients of foods i.e, onion uptake poisonous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…11 Moreover, Reyes-Vidal et al reported the potential of Ag/Zn nanoparticles in antimicrobial applications that up to 98% of inhibition of bacterial growth was achieved after 30 min of contact time. 10 Various approaches have been proposed to prepare bimetallic nanoparticles including a galvanic replacement reaction, 5 electrodeposition and redox replacement, 13,14 colloidal synthesis, 6 calcination, 9 electrodeposition, 10 and coreduction of metal ions. 15 Among these methods, the electrodeposition and redox replacement (EDRR) method is of great interest because it offers the possibility to control the size and composition of bimetallic nanoparticleswhich have significant impact on their properties and functionalitiesin a facile manner.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Moreover, Reyes-Vidal et al reported the potential of Ag/Zn nanoparticles in antimicrobial applications that up to 98% of inhibition of bacterial growth was achieved after 30 min of contact time. 10 Various approaches have been proposed to prepare bimetallic nanoparticles including a galvanic replacement reaction, 5 electrodeposition and redox replacement, 13,14 colloidal synthesis, 6 calcination, 9 electrodeposition, 10 and coreduction of metal ions. 15 Among these methods, the electrodeposition and redox replacement (EDRR) method is of great interest because it offers the possibility to control the size and composition of bimetallic nanoparticleswhich have significant impact on their properties and functionalitiesin a facile manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, the production of silver-based metallic nanoparticles has been an attractive field due to their superior conductive, optical, catalytic, and especially antimicrobial properties . The possibility of obtaining multifunctionality/enhanced properties by selecting the appropriate metal combinations has intrigued the investigation with broad bimetallic systems such as Ag/Pt, Ag/Au, Ag/Pd, Ag/Cu, Ag/Ni, Ag/Zn, , and Ag/Fe with the target of achieving new bifunctional or synergistic effects. For instance, Ag/Zn doped TiO 2 photocatalyst was found to have high efficiency toward ethyl phydroxybenzoate removal by photocatalysis (99.1% degradation within 2 h) .…”
Section: Introductionmentioning
confidence: 99%
“…The spectra of the formation of the Au-Ag core-shell composite nanoparticles were conrmed using the literature. 32,33,36 As shown in Fig. 7(e), aer the addition of L-cysteine into the bimetallic composite nanoparticle solution, the slight changes were observed in the spectra.…”
Section: Resultsmentioning
confidence: 80%
“…The citrate molecules over the surface of the bimetallic nanoparticles protect them from selfaggregation in aqueous solution due to steric hindrance and also support the binding of its carboxyl groups, resulting in repulsion between the bimetallic nanoparticles. 21,23,36 However, the addition of L-cysteine to the Au-Ag core-shell composite nanoparticles caused the color change from yellowish brown to light blue, and causes the broadening of SPR in the UV-vis region, as shown in Fig. 5(b).…”
Section: Sensing Mechanism Of the Au-ag Core-shell Composite Nanoparticles As A Plasmonic Chemical Probementioning
confidence: 99%
“…Metal combinations are another important subject that has been in the attention of researchers due to their new characteristics different from the properties of the components (Dobrucka et al, 2021). Green synthesized bimetallic Au-Ag nanoparticles have interesting properties and higher catalytic efficiencies than Au and Ag monometallic nanoparticles (Sahu et al, 2020). Ten years before the beginning of the nano-ecotoxicology field, researchers said that NPs can have a negative effect on biota by generating ROS (Khan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%